Because they hate : a survivor of Islamic terror warns America - Gabriel, Brigitte (New York : St. Martin's Griffin, 2006)
A Christian-Arab journalist recalls her eyewitness to the deadly beginnings of fundamentalist Islam as her family spent seven years in an underground bomb shelter in order to survive a jihad against non-Muslim people.
Peace before the rage -- My 9/11 -- Life under terror -- Hopeless existence -- A life-changing experience -- Rebuilding our lives -- Clash of civilizations -- Terrorists among us -- The toxic tsunami of hate -- The ivy-covered fifth column: Islamic influence alive and well on American campuses -- Bull's-eye of the Middle East -- Societies are not created equal -- Is Islam a peaceful religion? -- Political correctness gone mad.
Originally published: New York: St. Martin's, 2006.
Includes bibliographical references.
Keywords: Terrorism -- Lebanon; Victims of terrorism -- Lebanon; Terrorism -- Religious aspects -- Islam